MODEL PEMBELAJARAN STEAM UNTUK MENINGKATKAN HASIL BELAJAR IPA DAN KEAKTIFAN SISWA KELAS VI SD - Sholihah, Naf’atush; Suhada, Dadang; Khoimatun, Khoimatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The low student learning outcomes and students' lack of activity during the learning process is because learning is still teacher-centered This research aims (1) to determine the application of the Science, Technology, Engineering, Art and Mathematics (STEAM) learning model, (2) to determine the increase in student learning outcomes after implementing the STEAM learning model  in science learning, (3) To determine the increase in the activity of class VI students at SDN 1 Tenajar Kidul. after applying the STEAM learning model to science learning. The method used is Classroom Action Research (PTK), a design model from Kemmis and MC Taggrart. Where research is carried out in several stages, namely: planning, implementation, observation, then reflection. This research was applied to 25 grade 6 elementary school students consisting of 8 students and 17 female students. Improving learning outcomes and student activity using the STEAM learning model in science learning content for grade 6 elementary school has been carried out in 3 research cycles. This increase can be seen from the test results and is reinforced by observing student activity. The average pre-cycle student learning outcome was 54,84  with a completeness percentage of 40%, increased in the first cycle to 71,4 with a completeness percentage of 56%, and in the second cycle it increased to 73,2 with a completeness percentage of 72%, and was said to meet the indications of achievement in the third cycle on average. -average 88,24 with a completion percentage of 88%.